Prevalence and Characteristics of Neuroinfectious Disease Inquiries Within the Emerging Infections Network: A 22-Year Retrospective Study. (9th May 2020) - Matthews, Elizabeth; Diaz-Arias, Luisa A; Beekmann, Susan E; Polgreen, Philip; Waldrop, Greer; Yang, Vivian; Rimmer, Kathryn; Venkatesan, Arun; Thakur, Kiran T
Abstract: Background: To monitor emerging infectious diseases, the Centers for Disease Control and Prevention and the Infectious Disease Society of America established the Emerging Infections Network (EIN), allowing infectious disease specialists to post inquiries about clinical cases. We describe the frequency and characteristics of neuroinfectious disease-related inquiries. Methods: The EIN listserv was retrospectively reviewed from February 1997 to December 2019 using search terms associated with neurologic diseases. We recorded case summaries, disease type (ie, meningitis, encephalitis), inquiry type (diagnostic approach, result interpretation, management decisions), unique patient populations, exposures, pathogens, ultimate diagnosis, and change in clinical care based on responses. Results: Of 2348 total inquiries, 285 (12.1%) related to neuroinfectious diseases. The majority involved meningitis (99, 34.7%) or encephalitis (56, 19.6%). One hundred fifteen inquiries (40%) related to management, 34 (12%) related to diagnostic workup, and 22 (8%) related to result interpretation. Eight (2.8%) specifically involved results of cerebrospinal fluid polymerase chain reaction testing. Sixty-three (22.1%) involved immunosuppressed patients (29 human immunodeficiency virus-positive cases [46%]). The most common pathogens were Treponema pallidum (19, 6.7%) and Cryptococcus neoformans (18, 6.3%). In 74 (25%) inquiries, patients had neurologic symptoms without a clear infection, 38 (51.3%) of which included noninfectious neurologic etiologies in the differential diagnosis. Conclusions: This study demonstrates the significant challenges of diagnosis and management of neuroinfectious diseases within the field of infectious diseases. It also highlights the importance of curated forums to guide the approach of difficult cases, in particular instances that mimic infectious diseases. Finally, the EIN listserv may assist in identifying areas for research and training to address these complexities. Abstract : This is an analysis of the Emerging Infection Network's listserv focused on clinical inquiries involving neuroinfectious diseases. The goal was to identify recurring themes and questions to help guide neuroinfectious disease-related education and research.